Building Business Performance through Partnership Strategy Model: Evidence from Renewable Energy Industry in Indonesia - Mustikaningsih, Dewi; Cahyandito, Martha Fani; Kaltum, Umi; Sarjana, Sri (International Journal of Energy Economics and Policy, 2019)
This research was carried out as an effort to encourage performance improvement of renewable energy power plants. The purpose of this study was conducted to measure the level of influence of strategic partnerships in creating better business performance in renewable energy industry companies in Indonesia. Strategic partnerships have an important role in developing business performance, including by encouraging dynamic capabilities, supply chains, and improving the regulatory system owned by the renewable energy business lines in Indonesia. Our previous research model that we published shows that regulation plays a very dominant role, then we modify it by issuing regulatory variables that uncontrollable by management. We try to see the effect of exogenous variables that can be fully controlled. Data related to renewable energy industry is collected and presented in this study for completeness. Test data using partial least square equipped with various supporting data obtained from government institutions and private sector that have sufficient information about renewable energy industry. The findings of this study state that to improve business performance, strategic partnerships need to be carried out optimally through various efforts including strengthening collaboration in aligning the supply chain and developing dynamic capabilities within the organization. For the future, it is expected that all stakeholders involved in the renewable electricity generation industry in Indonesia can improve their business performance so that they can increase electricity supply to remote villages and able to transform use of primary energy sources from fossils to environmentally friendly renewable energy where potential is widely spread throughout region so that sustainable life in the world is more awake. Keywords: Strategic Partnership, Business Performance, Supply Chain Performance, Renewable Energy Industry JEL Classifications: L, Q2, Q4 DOI: https://doi.org/10.32479/ijeep.7780